Kesesuaian butir soal buku Al-Qur’an Hadis kelas X Madrasah Aliyah dengan pendekatan HOTS dan LOTS dalam Kurikulum 2013.: The alignment of question items in the Al-Qur’an Hadith textbook for grade X of Madrasah Aliyah with HOTS and LOTS approaches in the 2013 Curriculum. - Nurul Azizah, Fadila; Nugraha, Mulyawan Safwandy (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
The integration of Higher Order Thinking Skills (HOTS) in assessment is crucial to achieving the 2013 Curriculum’s goal of fostering students’ critical, analytical, and evaluative competencies. However, in Islamic Religious Education, assessments often remain dominated by Lower Order Thinking Skills (LOTS), creating a gap between curricular aspirations and actual practice. This study aimed to analyze the cognitive levels of 124 test items in the Grade X Al-Qur’an Hadis textbook published by the Indonesian Ministry of Religious Affairs (2020), focusing on the distribution of HOTS and LOTS questions. Employing a qualitative descriptive design, document analysis was conducted using Bloom’s revised taxonomy to classify each item into C1–C6 cognitive levels. The findings revealed that 88.7% of items fell under LOTS (C1–C3), while only 11.3% met HOTS criteria (C4–C5), with no items at the C6 level. These results indicate that the textbook’s assessments largely measure basic knowledge and comprehension, limiting opportunities for higher-order cognitive engagement. The study implies an urgent need to reform question construction strategies in religious education materials to better align with curriculum goals, enhance critical and creative thinking, and support students’ readiness for complex problem-solving in contemporary contexts.